Impact of Warmer Sea Surface Temperature on the Global Pattern of Intense Convection: Insights From a Global Storm Resolving Model. Issue 16 (26th August 2022) - Cheng, Kai‐Yuan; Harris, Lucas; Bretherton, Christopher; Merlis, Timothy M.; Bolot, Maximilien; Zhou, Linjiong; Kaltenbaugh, Alex; Clark, Spencer; Fueglistaler, Stephan
Abstract: Intense convection (updrafts exceeding 10 m s −1 ) plays an essential role in severe weather and Earth's energy balance. Despite its importance, how the global pattern of intense convection changes in response to warmed climates remains unclear, as simulations from traditional climate models are too coarse to simulate intense convection. Here we use a kilometer‐scale global storm resolving model (GSRM) and conduct year‐long simulations of a control run, forced by analyzed sea surface temperature (SST), and one with a 4 K increase in SST. Comparisons show that the increased SST enhances the frequency of intense convection globally with large spatial and seasonal variations. Changes in the spatial pattern of intense convection are associated with changes in planetary circulation. Increases in the intense convection frequency do not necessarily reflect increases in convective available potential energy. The GSRM results are also compared with previously published traditional climate model projections. Plain Language Summary: Intense convection, which we experience as strong thunderstorms, is a major cause of damaging weather and an important component in Earth's energy balance. However, it is still unclear how intense convection changes in a warmed climate because traditional climate models cannot resolve these convective events. In order to investigate the impact of a warmed climate on intense convection, we use a new ultra‐high‐resolution global model to conduct year‐long simulations under normal and warmed‐ocean conditions. We find that intense convection becomes more frequent globally in a warmed climate. However, some regions have less intense convection. Spatial and seasonal responses of intense convection are associated with the changed planetary circulation. We also find that increases in an environmental measure of the favorability of the atmospheric state for convection do not necessarily favor the development of intense convection. Key Points: A global storm resolving model is used to conduct year‐long simulations to study the change of intense convection in a warmed climate Increased sea surface temperature modulates the frequency of intense convection with large spatial and seasonal variations Increases in convective available potential energy do not necessarily enhance intense convection frequency